Bio-based phase change material for enhanced building energy efficiency: A study of beech and thermally modified beech wood for wall structures - Grzybek, Jakub; Nazari, Meysam; Jebrane, Mohamed; Terziev, Nasko; Tippner, Jan; Petutschnigg, Alexander; Schnabel, Thomas (John Wiley & Sons, Inc., 2024)
This study investigated the impregnation of beech and thermally modified beech (TMB) with a ternary mixture of capric acid, palmitic acid, and stearic acid as a bio-based phase change material (BPCM). Finite element method (FEM) was used to complement the experimental analysis by providing new insights into computational methods for simulating the behavior of BPCMs in untreated and TMB. The analyzed specimens namely beech and TMB were impregnated with BPCM; the TMB achieved 54% weight percentage gain (WPG) while untreated beech got 37%. Accordingly, a greater increase in the latent heat was obtained for TMB up to 90 J/g, while for untreated beech with BPCM up to 75 J/g. Impregnated specimens absorbed less moisture at relative humidity of air above 50%, likely caused by the high uptake and hydrophobic nature of the BPCM. The study highlights the research gap in performing mathematical simulations on wood samples with BPCM using material thermal properties derived from differential scanning calorimetry or T-History analysis. It shows that the direct use of these values for simulations leads to unacceptable outputs that result in high errors. The root mean square error for untreated and TMB samples impregnated with BPCM was in the range from 1.06 to 3.1 while that for untreated samples was in the range from 0.57 to 0.87, indicating that the main challenge in simulating and characterizing the samples is due to the interaction of the phase change material with the wood structure.
Keywords: beech; finite element method; building constructions; latent heat storage; thermal mass,wood impregnation